Role of Innate Immune Factors in the Adjuvant Activity of Monophosphoryl Lipid A - Martin, Michael (American Society for Microbiology, 2003)
Monophosphoryl lipid A (MPL) is a nontoxic derivative of lipopolysaccharide (LPS) that exhibits adjuvant properties similar to those of the parent LPS molecule. However, the mechanism by which MPL initiates its immunostimulatory properties remains unclear. Due to the involvement of Toll-like receptors in recognizing and transducing intracellular signals in response to LPS, the aim of the present study was to determine the ability of MPL to utilize the Toll-like receptor 2 (TLR2) and TLR4. We provide evidence that MPL differentially utilizes TLR2 and TLR4 for the induction of tumor necrosis factor alpha, interleukin 10 (IL-10), and IL-12 by purified human monocytes as well as by human peripheral blood mononuclear cells. Assessment of NF-κB activity demonstrated that MPL utilized TLR2 and especially TLR4 for the activation of NF-κB p65 by human monocytes. In addition, stimulation of human monocytes by MPL led to an up-regulation of the costimulatory molecules CD80 and CD86, an effect that could be reduced by pretreatment of cells with a monoclonal antibody to TLR2 or TLR4. Analysis of MPL-induced activation of the extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein (MAP) kinases revealed that MPL utilized both TLR2 and TLR4 for the phosphorylation of ERK1/2, while TLR4 was the predominant receptor involved in the ability of MPL to phosphorylate p38. Moreover, using selective inhibitors for MAP kinase kinase (PD98059) and p38 (SB203580), we show that ERK1/2 exhibited differential effects on production of TNF-α and IL-12 p40 by human monocytes, whereas MPL-induced activation of p38 appeared to be predominantly involved in production of IL-10 and IL-12 p40 by MPL-stimulated monocytes. Taken together, these findings aid in understanding the cellular mechanisms by which MPL induces host cell activation and subsequent adjuvant properties.